A Comprehensive Review on Prospects of Polymeric Nanoparticles for Treatment of Diabetes Mellitus: Receptors-Ligands, In vitro & In vivo Studies - Jain, Arinjay; Dawre, Shilpa (Recent Patents on Nanotechnology, 2024)
As per International Diabetes Federation Report 2022, worldwide diabetes mellitus (DM) caused 6.7M moralities and 537M adults suffering from diabetes mellitus. It is a chronic condition due to β-cell destruction or insulin resistance that leads to insulin deficiency. This review discusses Type-1 DM and Type-2 DM pathophysiology in detail, with challenges in management and treatment. The toxicity issues of conventional drugs and insulin injections are complex to manage. Thus, there is a need for technological intervention. In recent years, nanotechnology has found a fruitful advancement of novel drug delivery systems that might potentially increase the efficacy of anti-diabetic drugs. Amongst nano-formulations, polymeric nanoparticles have been studied to enhance the bioavailability and efficacy of anti-diabetic drugs and insulin. In the present review, we summarized polymeric nanoparticles with different polymers utilized to deliver anti-diabetic drugs with in vitro and in vivo studies. Furthermore, this review also includes the role of receptors and ligands in diabetes mellitus and the utilization of receptor-ligand interaction to develop targeted nanoparticles. Additionally, we discussed the utility of nanoparticles for the delivery of phytoconstituents which aids in protecting the oxidative stress generated during diabetes mellitus. Atlast, this article also comprises of numerous patents that have been filed or granted for the delivery of antidiabetic and anticancer molecules for the treatment of diabetes mellitus and pancreatic cancer.
Keywords: T1DM